Severe Infantile Coarctation and Mid Aortic Stenosis in Williams Syndrome - Marina, Lousararian; Ana, Troglia; J, Cabrera María; E, Alday Luis (Journal of Cardiology and Cardiovascular Medicine, 2019)
We report a challenging patient with Williams syndrome and severe coarctation of the aorta. As in a few similar cases reported, several surgical and catheter interventions for recoarctation, intrastent intimal proliferation and stenosis of the left sub-clavian artery were required. Aortic patch angioplasty is planned for the future in a grower child.